Sweet justice : Georgia Gilmore and the Montgomery Bus Boycott - Rockliff, Mara (Random House Studio, 2022)
"A picture book biography about Georgia Gilmore, the woman whose cooking helped feed and fund the Montgomery bus boycott of 1956"--